Analisis Realokasi Anggaran Sebagai Solusi Penanganan Covid-19 dan Dampaknya Terhadap Mekanisme Pengadaan Barang/Jasa - Riri Habibah Romli; Etti Ernita Sembiring; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This qualitative study aims to analyze the reallocation of the budget used for handling Covid-19 and its impact on the mechanism for the procurement of goods/services. The Cimahi City Government in dealing with Covid-19 has reallocated and refocused the budget in accordance with Presidential Instruction No. 4 of 2020. The data sources used were primary data obtained directly from the research location, namely budget realization reports and interview. The results showed that the budget reallocation carried out by the City of Cimahi for the handling of Covid-19 was collected in Unexpected Expenditures (BTT) which increased to Rp195,019,861,779.71 from the original Rp3,711,042,182.17. Unexpected Expenditures (BTT) are used to accommodate unexpected spending needs in handling Covid-19, especially in the health, economic and social fields. Changes in the mechanism for the procurement of goods/services during the pandemic period are changes in the guidelines used and most of the process is carried out online.